Reconstructing more than 40 years soil re-distribution in two Taiwanese watersheds - Alexander Marthyn Borghuis; Yu-Jia Chiu (European Regional Science Association (ERSA), 2005)
Taiwan is a little smaller than the Netherlands, an island surrounded by the sea and has a population of circa 23 million. Add a central range of steep mountains and it is clear that the pressure on living space and natural resources is enormous. This is exemplified by the fact that Taiwan has become one of the countries facing water scarcity in the next decades. Taiwan has around 40 large reservoirs that hold around 4200 million cubic meter of all water, a recent study shows that around 300 million cubic meter of silt accumulates in Taiwan's reservoirs and further that only around 10% of sediment is removed each year. Therefore, reservoir management tries to counter the sedimentation problem at the source. However, for effective measures reliable data on the origins of the sediment and patterns and rates of erosion in the hinterland are needed. It is for example not well established what the effect is of the annual tropical cyclones on erosion rates of undisturbed steep forested slope land soils. Therefore, the authors present a novel method that aims at reconstructing more than 40 years of soil erosion and deposition within the two largest reservoir catchments in Taiwan. The method combines the Cs-137 isotope technique, widely used to calculate soil re-distribution rates with a detailed representation of the watersheds in a GIS. More than 160 soil profile samples were collected in both undisturbed (forested) and disturbed (agricultural) locations across the watersheds. The sampling was based on an a priori stratification of the watersheds into landscape units that were assumed to have distinct ranges of soil re-distribution. Cs-137 activity levels in the soil profiles were measured in a radiological laboratory. Published conversion techniques were applied to compute soil re-distribution rates for observed Cs-137 inventories. Geo-statistical methods were then applied to obtain the relations between re-distribution rates and landscape units. These relations were then distributed using the GIS representation of the landscape units. The GIS-embedded models were calibrated and cross-validated and show maps of 40 years soil erosion and deposition across the studied watersheds as well as a map of estimate uncertainties.
Keywords: 330